The Role of Brand Image as a Moderator in the Influence of Social Media, Online Prices, and Customer Reviews on Purchasing Decisions in E-Commerce - Evi Sirait; Riani Prihatini Ishak; Vera Selviana Adoe; Damaris Yvette Koli; Andry Mochamad Ramdan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of social media, online prices, and customer reviews on purchasing decisions in e-commerce with brand image as a moderating variable. The research method used is a quantitative approach with an associative research type. Data were collected by distributing questionnaires to consumers who have made purchases on e-commerce platforms, using a purposive sampling technique. Data analysis was conducted using the Partial Least Squares (PLS-SEM) method and Moderated Regression Analysis (MRA) to test the role of moderating variables. The results show that social media, online prices, and customer reviews partially and simultaneously have a positive and significant influence on purchasing decisions. Social media can increase purchasing interest through interactive and informative content, online prices are a primary consideration in choosing a product, while customer reviews play a role in building consumer trust. In addition, brand image is proven to moderate the relationship between social media, online prices, and customer reviews on purchasing decisions by strengthening the influence of all three variables. The conclusion of this study is that purchasing decisions in e-commerce are influenced by a combination of digital marketing factors and brand perceptions. Therefore, business actors are advised to optimize the use of social media, set competitive prices, manage customer reviews well, and build a strong brand image to increase consumer trust and loyalty.